Increasing cropping intensity, productivity and diversity of crops through rice based cropping pattern in Tangail (Bangladesh Journal of Agricultural Research, 2026)
The experiment was conducted at Farming Systems Research and Development site under On-Farm Research Division, Bangladesh Agricultural Research Institute, Tangail during the period of 2019-20 and 2000-21 having eight rice-based cropping patterns viz., Mustard-Boro-T. Aman rice, Potato-Boro-T. Aman, Mustard-T. Aus-T. Aman, Lentil- Jute-T. Aman, Wheat-Jute-T. Aman, Wheat-Sesame-T. Aman, Garden pea-Boro-T. Aman and Fallow-Boro-T. Aman (as check). The treatments were replicated five times in randomized complete block design with a plot size of 8.0 m  5.0 m. Result showed that the highest rice equivalent yield (31.77 t ha-1) was obtained from Potato-Boro-T. Aman cropping pattern which was followed by Garden pea-Boro-T. Aman cropping pattern (26.42 t ha-1). The lowest rice equivalent yield (11.37 t ha-1) was obtained from Fallow-Boro-T. Aman cropping pattern. Highest gross return (Tk. 557514 ha-1 and gross margin (Tk.260964 ha-1) and production efficiency (108.43 kg ha-1day-1) was recorded from Potato-Boro-T. Aman cropping pattern. Maximum land use efficiency (86%) was observed in Wheat-Jute-T. Aman cropping pattern. Highest benefit cost ratio was recorded from Mustard (var. BARI Sarisha-14)-Boro-T. Aman and Mustard (var. BARI Sarisha-18)-T. Aus-T. Aman pattern (2.16 and 2.13). On the other hand, highest by-product yield was obtained from Potato-Boro-T. Aman rice sequence. However, the higher sustainable yield index value was recorded in Potato-Boro-T. Aman rice (97.30%), which was closely followed by Garden pea-Boro-T. Aman (95.74%) and Mustard-Boro-T. Aman (93.3 %). The more labour (537man days ha-1) intensive cropping pattern was Potato-Boro-T. Aman rice. However, the profitable and viable cropping patterns were found Mustard-Boro-T. Aman followed by Potato-Boro-T. Aman and Garden pea-Boro-T. Aman which need to be disseminated in the farmer’s fields.Bangladesh J. Agril. Res. 47(4): 463-472, December 2022